Clone-Dependent Expression of Esca Disease Revealed by Leaf Metabolite Analysis - Moret, Florian; Lemaître-Guillier, Christelle; Grosjean, Claire; Clément, Gilles; Coelho, Christian; Negrel, Jonathan; Jacquens, Lucile; Morvan, Guillaume; Mouille, Grégory; Trouvelot, Sophie; Fontaine, Florence; Adrian, Marielle (Frontiers in Plant Science, 2019)
Grapevine Trunk Diseases, especially Esca, are of major concern since they gradually alter vineyards worldwide and cause heavy economic losses. The expression of Esca disease symptoms depends on several factors, including the grapevine cultivar. In this context, a possible clone-dependent expression of the Esca disease was studied. Two clones of ‘Chardonnay’ grown in the same plot were compared according to their developmental and physiological traits, metabolome, and foliar symptom expression. Analysis of their leaf metabolome highlighted differences related to symptom expression. Interestingly, the content of a few specific metabolites exhibited opposite variations in leaves of symptomatic shoots of clones 76 and 95. Altogether this study showed a clone-dependent expression of Esca disease in ‘Chardonnay’ and the relevance of GC-MS and 3D fluorescence methods to analyze the impact of the disease on the leaf metabolome.